DIALOG FILOSOFIS MAIMONIDES: JEJAK PEMIKIRAN AL-FĀRĀBI DALAM PANDANGAN RELASI FILSAFAT DAN AGAMA MAIMONIDES - Simplesius Sandur (Jurnal Filsafat dan Teologi Katolik, 2018)
The questions about relation between philosophy and religion always raise discussions among scholars and philosophers. It is not only about “philosophic” and “religious” problem but aslo extends to the truth and role of both in a society. Maimonides offers his solution to resolve this issue. He proposes a harmonization of both “truths” since they came from the same Source. In Maimonides’ mind, philosophy and religion have an essential role in establishing a society. Maimonides, of course, does not stand alone to resolve this probem. His main sources are Platonic and Aristotelian philosophy interpreted by Arabic masters in Arabic philosophical tradition particularly by Al-Fārābi. Maimonides tries as he can to analyze Judaism philosophically. He establishes his concept on relation between philosophy and religion on the thesis natural division of human beings.